The origins of language : unraveling evolutionary forces - Masataka, Nobuo (Springer, 2017)
The Gestural Theory of and the Vocal Theory of Language Origins Are Not Incompatible with One Another -- The Gestural Origins of Language -- World-View of Protolanguage Speakers as Inferred from Semantics of Sound Symbolic Words: A Case of Japanese Mimetics...